Knowledge, attitude and practice towards intestinal schistosomiasis among school-aged children and adults in Amhara Regional State, northwest Ethiopia. A cross-sectional study - Getaneh Alemu; Endalkachew Nibret; Arancha Amor; Abaineh Munshea; Melaku Anegagrie (Tropical Medicine and Health)
Abstract Background Schistosoma mansoni causes intestinal schistosomiasis (SCH) in all regions of Ethiopia. Despite many years of mass treatment, the prevalence has not dropped significantly. The reduction of SCH transmission demands the integration of deworming with safe water, sanitation, and hygiene (WASH) activities. Adequate knowledge and a positive attitude towards SCH are critical to practicing those interventions. However, data on the knowledge, attitude, and practice (KAP) level in school and community settings is limited in Ethiopia. Methods School and community-based cross-sectional studies were conducted from February to June 2023 among 634 school-aged children (SAC) and 558 adults. A pre-tested questionnaire was used to collect socio-demographic and KAP data. Records were entered and analyzed using SPSS software version 21. Correct responses for each of the KAP questions were scored as one, while incorrect or ‘I don’t know’ responses were scored as zero. Good knowledge, a positive attitude and good practice were declared if percentage scores were ≥ 80%, ≥ 90% and ≥ 75%, respectively. Results Only 229 (19.2%) respondents, comprising 91 (14.4%) SAC and 138 (24.7%) adults, had ever heard of SCH. Adults, males, and urban residents had higher awareness level compared to their respective counterparts (p < 0.05). Only 28.4% of aware respondents knew that swimming or bathing in freshwater is a risk factor for schistosoma infection; 10.9% knew the etiologic agent; and 14.4% mentioned at least one sign and symptom associated with SCH. The majority (97.8%) of the respondents were willing to take therapeutic drugs, but only 37.6% believed that SCH is a serious disease. Regarding risky practices, 89.5% practiced swimming or bathing in freshwater, and 25.3% had no access to piped water. Among the aware respondents, only 18 (7.9%) had good knowledge, while 30 (13.1%) had a positive attitude towards SCH. Ninety-nine (43.2%) respondents had good Schistosoma infection prevention practices. Conclusions The knowledge, attitude, and preventive practice level towards schistosomiasis are low in the study area. Therefore, strengthening school and community-based health education, along with mass drug administration (MDA), WASH, and a vector control program, is recommended for preventing SCH.